Microstructural characterization of layers produced by plasma nitriding on austenitic and superaustenitic stainless steel grades - Totten, George E.; Casteletti, Luiz C.; Fernandes, Frederico A.P.; Gallego, Juno [UNESP] (ASTM International, 2012)
High chromium content is responsible for the formation of a protective passive surface layer on austenitic stainless steels (ASS). Due to their larger amounts of chromium, superaustenitic stainless steels (SASS) can be chosen for applications with higher corrosion resistance requirements. However, both of them present low hardness and wear resistance that has limited their use for mechanical parts fabrication. Plasma nitriding is a very effective surface treatment for producing harder and wear resistant surface layers on these steel grades, without harming their corrosion resistance if low processing temperatures are employed. In this work UNS S31600 and UNS S31254 SASS samples were plasma nitrided in temperatures from 400 °C to 500 °C for 5 h with 80% H 2-20% N2 atmosphere at 600Pa. Nitrided layers were analyzed by optical (OM) and transmission electron microscopy (TEM), x-ray diffraction (XRD), and Vickers microhardness testing. Observations made by optical microscopy showed that N-rich layers were uniform but their thicknesses increased with higher nitriding temperatures. XRD analyses showed that lower temperature layers are mainly composed by expanded austenite, a metastable nitrogen supersaturated phase with excellent corrosion and tribological properties. Samples nitrided at 400 °C produced a 5 μm thick expanded austenite layer. The nitrided layer reached 25 lm in specimens treated at 500 °C. There are indications that other phases are formed during higher temperature nitriding but XRD analysis was not able to determine that phases are iron and/or chromium nitrides, which are responsible for increasing hardness from 850 up to 1100 HV. In fact, observations made by TEM have indicated that formation of fine nitrides, virtually not identified by XRD technique, can begin at lower temperatures and their growth is affected by both thermodynamical and kinetics reasons. Copyright © 2012 by ASTM International.
Keywords: Expanded austenite; Microstructure; Plasma nitriding; TEM analysis; XRD; Austenitic; Chromium nitride; Low hardness; Low processing temperature; Mechanical parts; Micro-structural characterization; N2 atmospheres; Nitrided; Nitrided layer; Nitriding temperatures; Passive surfaces; Plasma nitrided; Resistance requirements; Steel grades; Superaustenitic stainless steel; Supersaturated phase; Surface layers; Temperature layers; Transmission electron microscopy tem; Tribological properties; Vickers microhardness; Wear resistant; XRD analysis; XRD technique; Austenite; Austenitic stainless steel; Chromium; Corrosion resistance; Growth kinetics; Hardness; Nitrides; Nitriding; Nitrogen plasma; Optical microscopy; Plasma applications; Surface treatment; Transmission electron microscopy; Wear resistance; X ray diffraction; Atmospheric temperature